2019
DOI: 10.1177/2045125319862968
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of psychoses in patients with epilepsy: an update

Abstract: Psychotic disorders represent a relatively rare but serious comorbidity in epilepsy. Current epidemiological studies are showing a point prevalence of 5.6% in unselected samples of people with epilepsy going up to 7% in patients with temporal lobe epilepsy, with a pooled odds ratio of 7.8 as compared with the general population. This is a narrative review of the most recent updates in the management of psychotic disorders in epilepsy, taking into account the clinical scenarios where psychotic symptoms occur in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 60 publications
0
44
1
6
Order By: Relevance
“…The most frequent type of seizures were complex focal seizures. AP/FN is rare in patients with mainly generalized tonic-clonic seizures and in extra-temporal lobe epilepsy (Agrawal and Mula, 2019).…”
Section: Type Of Epilepsymentioning
confidence: 99%
See 2 more Smart Citations
“…The most frequent type of seizures were complex focal seizures. AP/FN is rare in patients with mainly generalized tonic-clonic seizures and in extra-temporal lobe epilepsy (Agrawal and Mula, 2019).…”
Section: Type Of Epilepsymentioning
confidence: 99%
“…With regard to the clinical presentation, no new findings have emerged in recent years. The clinical presentation is nonspecific and there are no generally agreed diagnostic criteria for AP/FN (Agrawal and Mula, 2019). AP/FN generally presents with behavioral disturbances of acute or subacute onset, associated with thought disorder, delusions, hallucinations, significant mood change (hypomania or depression), and anxiety with depersonalization or derealization symptoms.…”
Section: Clinical Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuropsychiatric disorders such as mood, anxiety and psychotic disorders are observed in about 30-70% of TLE patients and these comorbidities have a significant impact on the patient's quality of life (6)(7)(8). In TLE, comorbid depression has the highest prevalence (42.9%) followed by anxiety disorders (18.4%), especially generalized anxiety disorder (GAD), while psychosis shows a lower prevalence (around 5-7%) (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between epilepsy and psychosis is multifaceted and probably related to a wide range of different mechanisms. It can be highlighted, for example, that neuroimaging studies in schizophrenia have shown abnormalities in brain networks overlapping those involved in temporal lobe epilepsy, particularly in the amygdala and the hippocampus (Agrawal & Mula, 2019).…”
Section: Discussionmentioning
confidence: 99%